Natural and Synthetic Compounds for Management, Prevention and Treatment of Obesity, 2nd Edition - Lauricella, Marianna; D'Anneo, Antonella (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint represents a collection of 12 scientific papers belonging to the Special Issue in International Journal of Molecular Sciences titled "Natural and Synthetic Compounds for Management, Prevention and Treatment of Obesity, 2nd Edition". Obesity is a serious global health problem with a high incidence of mortality and morbidity. Many drivers have been identified for its etiopathogenesis, such as excessive food intake, reduced physical activity and genetic predisposition. Adipose tissue is considered an endocrine organ producing multiple immune-modulatory proteins, known as adipokines with a pro-inflammatory or anti-inflammatory nature. An unbalanced production of adipokines with a pro-inflammatory role in adipose tissue induces low-grade systemic inflammation in obese patients, which predisposes them to insulin resistance, type II diabetes, cardiovascular disorders, and cancer. Nowadays, there has been a growing interest in finding novel target compounds, both natural and synthetic, with potential action against obesity. This reprint explores the mechanisms underlying the etiopathogenesis of obesity and related diseases and aims to identify new therapeutic strategy. In particular, the reprint focuses on the role of natural and synthetic compounds for the Management, Prevention and Treatment of Obesity. We thank all the authors for their contribution to the research topic of this reprint and all editorial staff for its valuable support.